(untitled) (Journal of Forensic Medicine & Toxicology, 2017)
Skill-based forensic training is an urgent need of forensic medicine department all over of the world to provide quality services. There is a gap in forensic knowledge and practice due to resource material, teaching methods, faculty resource development and training, unplanned training of faculty, arbitrariness in subject coverage, pattern of assessment of PG especially of clinical and surgical skills, poor working stations and primitive infrastructure available to them.